PENATALAKSANAAN FISIOTERAPI PADA KONDISI ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) DENGAN METODE NEURO SENSO MOTOR REFLEX DEVELOPMENT DAN PLAY THERAPYDI YPAC SURAKARTA - Hertina Yulianasari; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Attention Deficit Hyperactivity Disorder (ADHD) is a behavioral disorder characterized by concentration disorders and impaired concentration, and delayed speech in patients. Factors influencing the occurrence of ADHD are factors prenatal and postnatal prenatal complications, and environmental factors. Problematic on ADHD condition of postural hypotonus, spasm in M. Extensor Trunk, M. Trapesiuz Upper and M. Gastrocnemius, presence of postural hypotonus, sensory impairment with sensory blast, behavioral disorder, presence of reflux, Presence of functional activity disorder.Physiotherapy modalities that used under ADHD conditions are by administering NeuroSenso Motor Reflex Development &Syncronization modalities and play therapy. In this research use descriptive analytic method, and research design used is case study design. After 6 treatments (1)There is a change of postural tone from sitting 2 seconds to 15 seconds, standing 5 seconds to 10 seconds. (2) there was a decrease of spasm in M. Extensor Trunk, M. Trapesiuz Upper and M. Gastrocnemius on T4-T6. (3) There is a change in sensory examination of visual, auditory, tactile, touch, vestibular, and propioceptive on T4-T6. (4) There is a change in the examination of moro reflex, graps, stnr toward extension and extensor thrust on T4-T6. (5) There is a change in the examination of ADHD Test on T6.From the results obtained can be concluded that using the intervention of physiotherapy with NeuroSenso Motor Reflex Development &Syncronizationmodality and play therapy can help reduce the problems that arise in Attention Deficit Hyperactyvity Disorder (ADHD).